Heterogeneity in the Effects of Food Vouchers on Nutrition Among Low-Income Adults: A Quantile Regression Analysis. Issue 2 (February 2021) - White, Justin S.; Vasconcelos, Gabriel; Harding, Matthew; Carroll, Mandy M.; Gardner, Christopher D.; Basu, Sanjay; Seligman, Hilary K.
Purpose: To determine whether baseline fruit and vegetable (FV) intake or other predictors are associated with response to food vouchers (change in FV intake) among low-income adults. Design: Secondary analysis of a randomized, 2 x 2-factorial, community-based trial. Setting: San Francisco, California. Subjects: 359 low-income adults aged ≥21 years old. Intervention: Participants were mailed $20 of food vouchers monthly for 6 months, and randomized to 1 of 4 arms according to: eligible foods (FV only or any foods) and redemption schedule (weekly or monthly). Measures: Change in FV intake measured in cup equivalents between baseline and month 6 of the trial, based on 24-hour dietary recalls. Analysis: Quantile multivariate regressions were employed to measure associations between key predictors and change in FV intake across study arms. Results: FV-only weekly vouchers were associated with increased FV intake at the 25th percentile (0.24 cups/day, p = 0.048) and 50th percentile (0.37 cups/day, p = 0.02) of the distribution, but not at lower and higher quantiles. Response to the vouchers diminished 0.10 cups/day for each additional household member ( p = 0.02). Conclusion: Response to food vouchers varied along the FV intake distribution, pointing to some more responsive groups and others potentially needing additional support to increase FV intake. Larger households likely need vouchers of higher dollar value to result in similar changes in dietary intake as that observed in smaller households.